Evolutionary Relationships of the Phytophthora 1a Subclade Species Based on Complete Mitogenomes, and Novel Markers for Their Differentiation - Tao Lin; Huiqin Wang; Haiting Ma; Jiaying Duan; Wenxin Wang; Xiaoyu Shi; Yaling Li; Zengqiang Qian; Nian Liu; Jiabin Zou; Ayaka Hieno; Koji Kageyama; et al. (Ecology and Evolution)
ABSTRACT Phytophthora is a genus of oomycetes that includes many aggressive pathogens capable of devastating farmlands and forests worldwide. Among the oldest and most well‐known species, P. cactorum exhibits morphological and genetic similarities to other homothallic species within subclade 1a, which complicates the understanding of their evolutionary relationships. This study primarily compared seven P. cactorum strains from diverse origins with three closely related species in subclade 1a, utilizing mitogenome sequences for analysis. The circular mitogenomes of the four species were nearly identical in size and comprised 38 protein‐coding genes (PCGs), 25 transfer ribonucleic acid genes, and 2 ribosomal RNA genes. The mitochondrial genomes exhibited a higher percentage of A/T compared to G/C content. The majority of AT‐skew and GC‐skew values among the 38 PCGs were positive, with the AT‐skew demonstrating a more pronounced bias than the GC‐skew. The Ka/Ks ratios revealed that 35 PCGs underwent significant purifying selection. Although the AliGROOVE analysis indicated notable similarities among the subclade 1a species, four PCGs exhibited significantly higher pairing frequency compared to the complete mitogenome. The results from the phylogenetic analysis aligned with the pairwise genetic distances, indicating that P. cactorum is more closely related to P. pseudotsugae than to P. hedraiandra. Furthermore, we found that the nad9 gene is informative to differentiate closely related Phytophthora species within subclade 1a, akin to the cox1 gene.